Gal-3 Deficiency Suppresses Novosphyngobium aromaticivorans Inflammasome Activation and IL-17 Driven Autoimmune Cholangitis in Mice - Arsenijevic, Aleksandar; Milovanovic, Jelena; Stojanovic, Bojana; Djordjevic, Dragana; Stanojevic, Ivan; Jankovic, Nenad; Vojvodic, Danilo; Arsenijevic, Nebojsa; Lukic, Miodrag L.; Milovanovic, Marija (Frontiers in Immunology, 2019)
Gal-3 has the role in multiple inflammatory pathways. Multiple-hit etiology of primary biliary cholangitis (PBC) and evolving immune response at various stages of the disease includes involvement of Gal-3 in PBC pathogenesis. In this study we aimed to clarify the role of Gal-3 in Novosphingobium aromaticivorans (N. aromaticivorans) induced biliary disease. Autoimmune cholangitis was induced in mice by two intra-peritoneal injections of N. aromaticivorans within 2 weeks. The role of Gal-3 was evaluated by using Lgals3−/− mice and mice treated with Gal-3 inhibitor. The histological and serological parameters of disease, phenotype of dendritic, NK, NKT, and T cells and inflammasome expression were evaluated. Marked attenuation of the disease in Lgals3−/− and Gal-3 inhibitor, DAVANAT®, treated mice is manifested by the absence of bile duct damage, granulomas and fibrosis. Liver infiltrates of N. aromaticivorans infected wild type mice had higher incidence of pro-inflammatory macrophages, dendritic cells, NK, NKT, and T cells. Lgals3 deletion and treatment with Gal-3 inhibitor reduced inflammatory mononuclear cell infiltrate, expression of NLRP3 inflammasome in the liver infiltrates and interleukin-1β (IL-1β) production in the livers of N. aromaticivorans infected mice. In vitro stimulation of wild type peritoneal macrophages with N. aromaticivorans caused increased NLRP3 expression, caspase-1 activity and IL-1β production compared with Lgals3−/− cells. Our data highlight the importance of Gal-3 in promotion of inflammation in N. aromaticivorans induced PBC by enhancing the activation of NLRP3 inflammasome and production of IL-1β and indicate Gal-3 as possible therapeutical target in autoimmune cholangitis. Galectin-3 appears involved in inflammatory response to gut commensal leading to PBC.